Pengaruh Kepemilikan Saham, Pertumbuhan Perusahaan, dan Struktur Modal terhadap Financial Distress PT. Sritex 2017–2024 - Salma Safina; Erna Puspita; Diah Nurdiwaty (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of share ownership structure, firm growth, and capital structure on the potential for financial distress at PT Sritex during the 2017–2024 period. Method: This study used secondary data and adopted a quantitative approach. The research object was PT Sritex during the 2017–2024 period. The data were obtained from the company's published financial statements and processed into 31 observations for analysis. Analysis was performed using multiple linear regression using IMB SPSS software. Finding: The findings reveal that share ownership structure and firm growth do not significantly influence the potential for financial distress when examined individually. In contrast, capital structure has a significant influence on the potential for financial distress. Furthermore, the results show that share ownership structure, firm growth, and capital structure jointly have a significant effect on the potential for financial distress at PT Sritex during the 2018–2024 period. Novelty: This study contributes to the existing literature by focusing exclusively on PT Sritex during the 2017–2024 period. Unlike most previous studies that employ cross-sectional data from multiple companies, this research adopts a single-company approach, allowing for a more comprehensive analysis of how share ownership structure, firm growth, and capital structure influence financial distress.